Phraseological Transformations in Classical Works of English and Russian Literature - Nailevna Salieva, Rimma (2021)
The article aims to reveal and analyze phraseological paradigm of transformed PUs in the context within two remote cognates.  The following problems arise: 1) detection and analysis of semantics and semantic structure of transformed phraseological units; 2) allocation of general features of using such PUs in the context; 3) investigation of functioning of such PUs in classical works of English and Russian literature. Semantic, grammatical, componential and contextual aspects of using such phraseological units are analyzed in the present research. The paper presents the analysis and comparison of such linguistic systems as semantic macro and micro structures of PUs in English and Russian languages. The meaning of a PU presents a combination of two major macro components: 1) significative and denotative meaning and 2) connotative meaning. The semantic analysis of PUs gives us a fundamental understanding of existing of such micro components of meaning as estimation, emotionality, expressiveness and functioning in the context within the whole structure of meaning.